2014
DOI: 10.1007/s12035-014-8950-z
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of β-Asarone Against 6-Hydroxy Dopamine-Induced Parkinsonism via JNK/Bcl-2/Beclin-1 Pathway

Abstract: β-asarone, a major component of Acorus tatarinowii Schott, has positive effects in neurodegeneration disease, however, its effect on the Parkinson's disease (PD) remains unclear. In this study, the effects of β-asarone on behavioral tests, neurotransmitters, tyrosine hydroxylase (TH), and α-synuclein (α-syn) were investigated in 6-hydroxydopamine (6-OHDA) induced rats. Furthermore, the JNK/Bcl-2/Beclin-1 autophagy pathway was also studied. The results showed that β-asarone improved the behavioral symptoms of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 50 publications
1
24
1
Order By: Relevance
“…Our results showed significant alleviation of striatal dopamine level following B[a]P administration and the result finds support from previous report [ 20 ]. Similarly, 6-OHDA administration leads to significant decrease in dopamine level as compared to B[a]P and the above findings are in agreement with previous report [ 34 , 35 ]. The possible effect of neonatal B[a]P administration on striatal dopamine level during adolescence was found to be linked with the effect of 6-OHDA.…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed significant alleviation of striatal dopamine level following B[a]P administration and the result finds support from previous report [ 20 ]. Similarly, 6-OHDA administration leads to significant decrease in dopamine level as compared to B[a]P and the above findings are in agreement with previous report [ 34 , 35 ]. The possible effect of neonatal B[a]P administration on striatal dopamine level during adolescence was found to be linked with the effect of 6-OHDA.…”
Section: Discussionsupporting
confidence: 93%
“…In this respect, it should be stressed that JNKs can be activated by a number of factors implicated in PD such as toxicants [ 16 ] and unfolded/misfolded proteins [ 17 ]. Some studies have demonstrated that JNKs are significantly activated in several common animal models of PD induced by neurotoxins such as MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine), 6-OHDA (6-hydroxydopamine) or LPS (lipopolysaccharide) [ 18 , 19 , 20 , 21 ]. Genetic deletion of JNK2 and JNK3 protects against MPTP-induced neurodegeneration in mice [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…30,31 Furthermore, our previous results also suggested that b-asarone showed neuroprotective effects on 6-hydroxydopamine (6-OHDA) induced parkinsonian rats. 32 We also found that basarone and L-dopa co-administration could increase striatal levels of L-dopa and DA in healthy rats. 33 However, the effects on neurotransmitters, BBB and P-gp after co-administration treatment of b-asarone and L-dopa in the 6-OHDA induced PD rats have not been reported before.…”
Section: Introductionmentioning
confidence: 51%
“…Some studies proposed that β ‐asarone effectively reversed multi‐drug resistance (MDR) by inhibiting P‐gp function and expression in Caco‐2 cells as well as reduced P‐gp expression in prefrontal cortex in pentylenetetrazol kindling rats . Furthermore, our previous results also suggested that β ‐asarone showed neuroprotective effects on 6‐hydroxydopamine (6‐OHDA) induced parkinsonian rats . We also found that β ‐asarone and L‐dopa co‐administration could increase striatal levels of L‐dopa and DA in healthy rats .…”
Section: Introductionmentioning
confidence: 74%